Odpowiedzi

2010-02-15T19:47:34+01:00
3x + y = 2y + 7/-2y
x - y = 2x + y

3x-y = 7
x-y=2x+y/-y

3x-y = 7
x-2y=2x/-x

3x-y = 7
-2y=x

3*(-2y)=7
x=-2y

-6y=7:(-6)
x=-2y

y=-7/6
x=14/6

Taki musi wyjsc wynik minus siedem szóstych i czternascie szóstych
2010-02-15T19:49:13+01:00
3x + y = 2y + 7
x - y = 2x + y

3x-y=7
-x-2y=0 /*3

3x-y=7
-3x-6y=0 /+

-7y=7 /:7
y=-7

3x-(-7)=7
3x=0
x=0
y=-7
Najlepsza Odpowiedź!
2010-02-15T19:50:41+01:00
3x + y= 2y +7
x - y = 2x +y

3x + y - 2y = 7
x - y -2x - y = 0

3x - y = 7
-x - 2y = 0 |*3

3x - y =7
-3x - 6y = 0

-7y = 7 \ -7
y = -1

3x - (-1) = 7
3x + 1 = 7
3x = 7 - 1
3x = 6 \3
x = 2